PENGARUH ETOS KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR KEMENTRIAN AGAMA KOTA BATU - Salsabil Maulidia Luthfia; Abdul Qodir Djaelani; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT This research aims to: (a) Know partially the influence of work ethic , work discipline and organizational commitment on employee performance Ministry of Religious Office of Batu City. (b) Knowing simultaneously the influence of work ethic, work discipline and organizational commitment on employee performance Ministry of Religious office of Batu City. This research is a descriptive research with quantitative approach. The data source of this research is the dissemination of the list of statements (questionnaires) and interviews directly to employees of the Office of the Ministry of Religious City of Batu. The data used is primary data. This analysis is done by using SPSS program. The research of this study is to determine the influence of work ethic, work discipline and organizational commitment partially and simultaneously to the performance of employees of the Office of the Ministry of Religious City of Batu. The results of this study indicate that work ethic, work discipline and organizational commitment affect the performance of employees of the Office of the Ministry of Religious City of Batu.Keywords: Work Ethic; Work Discipline; Organizational Commitment; Employee performance